Bibliometric Analysis of Publication Paper Themes for Hajj Services over the Period of COVID-19 Pandemic - Abdullah Haidar; Siti Annisa Satifa (Sekolah Tinggi Agama islam Negeri Majene, 2023)
The expansion of the literature is necessary. A significance of the framework of the current condition of Hajj service development is required. This study aims to provide an overview of the publication activities and trend of research in relation to Hajj services using bibliometric analysis. The method in this research used descriptive statistical tools with meta-analysis employing bibliometric analysis of secondary data from 142 papers published during the period of the COVID-19 pandemic, from 2019 to 2022. The development trends of hajj service publications were also evaluated using the VOSviewer program. This study found that the number of research publications on the Hajj services has increased in the last four years (2019-2022) indicating that themes regarding Hajj services show uptrend patterns. These seem to lead scholars to provide contributions to the body of knowledge. In addition, the interest of scholars has been shifting toward topics related to digitalization systems.